OBAVEZE ERGA OMNES – JUS COGENS U NASTAJANJU? ANALIZA INSPIRISANA KNJIGOM THE NATURE OF INTERNATIONAL LAW - Zdravković, Ana (Pravni zapisi, 2021)
This paper is a follow-up to a debate on the book “The Nature of International Law” by Miodrag A. Jovanović. First, the approach towards erga omnes obligations adopted in the book is analyzed, after which a different perspective towards the concept is offered. The curious case of erga omnes obligations can be summed up by stating that there has hardly been more elucidated concept in international law but with so little clarification achieved. With the aim of shedding more light on this conundrum, the concept is compared to others of a similar nature, primarily jus cogens norms, only to identify that erga omnes obligations could be defined as jus cogens in statu nascendi. Respectively, it is argued that according to the current state of affairs in the international community, the International Court of Justice is an instance of last resort when distinguishing between jus cogens norms and obligations erga omnes. Finally, the view concerning the three-layered nature of the international legal hierarchy is accepted, with jus cogens norms having the highest rank, followed by erga omnes obligations and with the jus dispositivum of international law in third place.
Keywords: erga omnes obligations; jus cogens; peremptory norms of international law; International Court of Justice; International Law Commission